2016
DOI: 10.22159/ajpcr.2017.v10i1.16196
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity Evaluation of Ethanol Extract of Curcuma Mangga Rhizome

Abstract: Objective: Curcuma mangga is highly valued in traditional medicines. This study was carried out to evaluate the in vivo acute toxicity of C. mangga.Methods: Acute toxicity of ethanol extract of C. mangga rhizome was evaluated in mice. The extract at a single dose of 500, 1000, 2000 and 5000 mg/kg body weight (BW) were orally administered to the test animal. Signs of toxicity, BW and mortality were observed for 14 days. The macropathology and histopathology examination was also performed. Results:The highest do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Levamisole was used as a positive control. The result was in accordance with the previous study which showed the ability of C. mangga methanol extract to increase the phagocytosis response by in vitro and in vivo study 14,20 .…”
Section: Analysis Of Compounds and Mmunostimulatorysupporting
confidence: 92%
See 2 more Smart Citations
“…Levamisole was used as a positive control. The result was in accordance with the previous study which showed the ability of C. mangga methanol extract to increase the phagocytosis response by in vitro and in vivo study 14,20 .…”
Section: Analysis Of Compounds and Mmunostimulatorysupporting
confidence: 92%
“…Quercetin is in the class of flavonoids which has been reported to have antioxidant activity 13 . Our in vivo study reported that C. mangga increased phagocytosis ability of mice leukocytes 14 . However, it is necessary to elaborate its immunomodulatory activity on adaptive immunity.…”
Section: Analysis Of Compounds and Mmunostimulatorymentioning
confidence: 74%
See 1 more Smart Citation
“…The antiinflammatory, immunomodulatory, antifungal, anticancer and nitric oxide inhibitory activities of C. mangga have also been reported [11][12][13][14] . Safety assessment revealed that it was untoxic in show short-term treatment 15 . The previous study has also shown the immunomodulatory properties of C. mangga 16 .…”
Section: Introductionmentioning
confidence: 99%